The role of women in the field of textile design towards development of Pakistani textile industry - Zahid, Umber; Kamaruddin, Zumahiran (International Journal of Children, Women, Elderly and Disable People, 2019)
Numerous readings suggest the gender-based perception of specialties in the related fields of textile design. This study aims to reveal the significant participation of women that contribute to shaping textile design practices within the Pakistani textile industry. The objective of this study is to determine if there is a role of women in the development of textile design in the industry. The researchers plotted the gender segregation of employees of numerous textile industries and design schools across Pakistan. Additionally, the value of gender-specific commodities produced by these industries were also analyzed, then used statistical tests to determine if there was a correlation. The results show that women play important role in the development of textile design in the fields of academics, professional practice and commodity range. For example, 72% of the textile design teachers, 75.5% of the textile design practitioners, and 88 % of the textile design students are women. These results impart endorsement to the notion that the women enjoy an eminent concern in the textile design profession, which is caused by the historic presence of women in the making of textiles. It is also evident from the history that most of the traditional textile crafts and practices are conceived, produced and used by women particularly the commodities related to the dowry practice in the Indian sub-continent. Understanding the factors influencing the role of women in making strategies for training, infrastructure improvement and enhanced consumer satisfaction will allow their involvement in decision making. This will help the Pakistani government to develop policies for workplace safety, social safety, entrepreneurship support, improved service structure, and enhanced incentives